BRAVE: A point of care adaptive leadership approach to providing patient-centric care in the emergency department - Fatimah Lateef; Kenneth Tan Boon Kiat; Md. Yunus; Mohamed Alwi Abdul Rahman; Sagar Galwankar; Hassan Al Thani; Amit Agrawal (Journal of Emergencies, Trauma and Shock, 2022)
The practice of emergency medicine has reached its cross roads. Emergency physicians (EPs) are managing many more time-dependent conditions, initiating complex treatments in the emergency department (ED), handling ethical and end of life care discussions upfront, and even performing procedures which used to be done only in critical care settings, in the resuscitation room. EPs manage a wide spectrum of patients, 24 h a day, which reflects the community and society they practice in. Besides the medical and “technical” issues to handle, they have to learn how to resolve confounding elements which their patients can present with. These may include social, financial, cultural, ethical, relationship, and even employment matters. EPs cannot overlook these, in order to provide holistic care. More and more emphasis is also now given to the social determinants of health. We, from the emergency medicine fraternity, are proposing a unique “BRAVE model,” as a mnemonic to assist in the provision of point of care, adaptive leadership at the bedside in the ED. This represents another useful tool for use in the current climate of the ED, where patients have higher expectations, need more patient-centric resolution and handling of their issues, looming against the background of a more complex society and world.